MIKROSIMULASI PENERAPAN TRANSJOGJA BUSWAY DAN TRANSJOGJA AREA TRAFFIC CONTROL SYSTEM (ATCS) - , ANUGRAH ILAHI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, Bus Transjogja Operation mixed with other vehicles, that pattern of operation of Bus Transjoga give impact for other vehicle and Bus Transjogja performance that are travel time and delay performance of Bus Transjogja, and influence on queues and delays for other vehicles. On the other hand have a plan to increase of Bus Transjogja performance, which want to apply a special line (busway), and give priority of traffic signals at the Signalized intersection (ATCS). In this research was conducted and compared four conditions of simulation, such as: existing, Busway, ATCS, and Busway with ATCS, so we know the impact, if that implemented on real condition. Simulation was conducted using microsimulation software AIMSUN 6.1. The result of this research showed that the schema changed of Bus trip Transjogja by using a special lane busway, ATCS, and busway with ATCS, the best performance signalized intersections obtained by applying the ATCS, that five of nine intersections experiencing queues and delays decreased at signalized intersections. Application of alternative by applying busway or busway with ATCS, were giving negative impact the performance of the intersection by increasing queues and delays, this can be due to a special lane for Bus Transjogja consuming paths of lane for users of private vehicles, so the capacity of the road for other vehicles traveling became smaller. Shortest Average Travel time occurred by Transjogja busway with ATCS 10' 45", with 41,23% of travel time reduction, 22.86% Followed by scenario busway and 14.15% in scenario ATCS. Shortest delay also occurred in busway with ATCS scenario, average delay 5' 38â with delay reduction 57.45%, 32.13% followed by busway scenario, and 19.90% in ATCS scenario.